Using different methods in teaching English - Azimbayeva Ranohon Yuldashevna (Genius Publishing Group, 2024)
This article explores the significance of employing diverse teaching methods in English language education. It examines various strategies such as communicative language teaching, task-based learning, and technology integration, highlighting their effectiveness in promoting language acquisition and proficiency. The study underscores the importance of incorporating multiple methodologies to cater to diverse learning styles and enhance student engagement and retention.
Keywords: English language teaching; diverse teaching methods; communicative language teaching